Current evaluation practices of diversity trainers in German-speaking countries. (4th May 2017) - Rohmann, Anette; Froncek, Benjamin; Mazziotta, Agostino; Piper, Verena
Abstract: Diversity training has been greatly expanded in recent years in order to help people deal with the challenges of increased social diversity. However, little is known about the systematic evaluation of diversity training. The present research surveyed 172 diversity trainers concerning their evaluation practices with regard to diversity training. Although outcome evaluation is considered an important goal of training evaluations, most diversity trainers conducted the evaluations themselves and focused mainly on trainees' self-reported attitudes towards the training as assessed (directly) after the implementation of the training. The results are discussed in terms of their practical implications for improving training evaluation.